Efforts to Improve the Spiritual and Social Attitudes of Primary School Students Using Digital Learning Media - Giantomi Muhammad; Basmah Junnatussadiah (Journal of Practice Learning and Educational Development, 2026)
Spiritual and social attitudes are interrelated. The manifestation of obedience to Allah SWT and carrying out His commands is embodied in spiritual attitudes. Meanwhile, mutual respect and appreciation as well as good social interaction are embodied in social attitudes. Similarly, the Islamic principle of amar makruf nahi munkar (enjoining what is good and forbidding what is evil) underscores the importance of social and spiritual attitudes. Therefore, efforts are needed to enhance the spiritual and social development of students, one of which is through the use of digital learning media. This study aims to analyse these two attitudes as applied using digital learning media. A qualitative approach with a case study method was employed at SD Matla’ul Khoeriyah in Bandung City. Research sources were obtained from the school principal, teachers, and students. Interviews, observations, and documentation were used as methods to collect data. The data was then analysed through collection, reduction, presentation, conclusion, and verification. The results of the study showed that the use of digital learning media effectively improved students' spiritual and social attitudes. In terms of spiritual attitudes, it enhances students' religiosity in school activities. Additionally, students' social attitudes emphasise a sense of camaraderie among peers, responsibility, and the habit of greeting others with a smile, greeting, politeness, and courtesy.